2022
DOI: 10.1158/1055-9965.epi-21-0991
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Performance of Two Stool DNA Tests and a Fecal Immunochemical Test in Detecting Colorectal Neoplasm: A Multicenter Diagnostic Study

Abstract: Background: The most widely used noninvasive screening tests for colorectal cancer are fecal occult blood tests. Stool DNA test was developed in recent years. However, direct comparative analyses of these tests within the same population are still sparse. Methods: A total of 2,842 participants who visited outpatient clinics or cancer screening centers were enrolled. Stool DNA test-I (KRAS, BMP3, NDRG4, and hemoglobin immunoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“… 13 The present study also revealed that sDNA has better sensitivity than FIT for detecting LGIN, AA, and ACN, with an overall sensitivity of FIT for AA of 41.7%, corresponding to the previously reported range of 27.0%–67.0%, while the FIT specificity was higher than that of the sDNA method, 27 which was consistent with the results of a previous study. 20 While the FIT and sDNA test results presented some fluctuation, 17 it can be stated that the risk of malignant transformation could be reduced by early lesion detection, and further colonoscopy is required to detect high-risk groups. 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 The present study also revealed that sDNA has better sensitivity than FIT for detecting LGIN, AA, and ACN, with an overall sensitivity of FIT for AA of 41.7%, corresponding to the previously reported range of 27.0%–67.0%, while the FIT specificity was higher than that of the sDNA method, 27 which was consistent with the results of a previous study. 20 While the FIT and sDNA test results presented some fluctuation, 17 it can be stated that the risk of malignant transformation could be reduced by early lesion detection, and further colonoscopy is required to detect high-risk groups. 28 …”
Section: Discussionmentioning
confidence: 99%
“… 18 Meanwhile, Sharma demonstrated that FIT is better than sDNA testing in reducing CRC incidence and mortality, 19 while Jin et al concluded that two sDNA tests represent no significant advantage over FIT. 20 …”
Section: Introductionmentioning
confidence: 99%
“…All experimental procedures related to the MT-sDNA tests [ KRAS mutation, NDRG4, BMP3 methylation and Fecal Immunochemical Test (FIT)] were carried out in the laboratory of NHH Technology (Hangzhou, China). The details regarding probes and primers, as well as the risk prediction algorithm were the same as those in a previously published article[ 13 ]. In this risk prediction model, a risk score is provided as a single output.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with miRNA, the DNA methylation biomarker is more stable and specific for each cancer type, and the whole process procedure for the DNA methylation test is simpler than that of the miRNA-based test; thus, DNA methylation is more suitable as a biomarker for the early detection of cancer than other biomarkers [ 11 ]. Up to now, various DNA methylation-based biomarkers for the early detection of gastrointestinal cancer have been reported [ 12 , 13 , 14 ], and several commercial kits for colorectal cancer (CRC) screening or early detection have been approved by the FDA and NMPA [ 15 , 16 , 17 ]. The successful application of DNA methylation markers in CRC early detection indicated that they may serve as a potential effective method for UGC detection.…”
Section: Introductionmentioning
confidence: 99%